Flow injection analysis for the photometric determination of promethazine-HCl in pure and pharmaceutical preparation via oxidation by persulphate using Ayah 3SX3-3D solar micro photometer (Baghdad Science Journal, 2013)
The first flow injection spectrophotometric method is characterized by its speed and sensitivity which have been developed for the determination of promethazine-HCl in pure and pharmaceutical preparation. It is based on the in situ detection of colored cationic radicals formed via oxidation of the drug with sodium persulphate to pinkish-red species and the same species was determined by using homemade Ayah 3SX3-3D solar flow injection photometer. Optimum conditions were obtained by using the high intensive green light emitted diode as a source. Linear dynamic range for the absorbance versus promethazine-HCl concentration was 0-7 mmol.L-1, with the correlation coefficient (r) was 0.9904 while the percentage linearity (r2%) was 98.09%. the L.O.Q was 3.97 µg/sample, while L.O.D (S/N=3) = 0.2407µg/sample (5 µmol.L-1) from the stepwise dilution for the minimum concentration of lowest concentration in the linear dynamic range of the calibration graph. The R.S.D% at 2 mmol.L-1 promethazine-HCl is less than 1% (eight replicates) using 150 µL sample volume. Throughput 30 sample.hr-1. The method was applied successfully for the determination of promethazine-HCl in pharmaceutical preparation. By using paired t-test it was shown that there was no significant difference between the proposed method and official method and on that basis the new method can be accepted as an alternative analytical method.